P95 Obstetric and maternal outcome of patients with hodgkin lymphoma diagnosed during pregnancy: results from the INCIP registry. (1st November 2019) - Maggen, C; Dierickx, D; Lugtenburg, P; Laenen, A; Cardonick, E; Shmakov, RG; Bellido Casado, M; Cabrera Garcia, A; Gziri, MM; Halaska, MJ; Ottevanger, PB; Van Calsteren, K; et al.
Abstract : Introduction/Background: The purpose of this study was to assess obstetric and maternal outcome of pregnant patients with diagnosis of Hodgkin lymphoma (HL) to guide physicians in clinical management. Methodology: Clinical data of pregnant patients diagnosed with HL between 1969 and 2018 were collected from the registry of the International Network on Cancer, Infertility and Pregnancy (INCIP). For survival analysis of classical HL treated with an ABVD-based regimen, non-pregnant controls were selected based on stage and prognostic score at diagnosis. Results: The median gestational age at diagnosis of 134 eligible patients was 20 weeks (range: 3–37). Antenatal chemotherapy was initiated in 53.7% of patients. Ten (7.5%) early pregnancies were terminated. One foetus deceased in the third trimester after three cycles of chemotherapy. In total, 120 (89.6%) pregnancies ended in a live birth. Preterm delivery was observed in 47 (40.1%) singleton pregnancies. Birth weight percentiles were lower in children prenatally exposed to oncological treatment and 17.9% were small for gestational age at birth (figure 1). Four children (3.5%) had major congenital malformations. Five-year progression-free survival (PFS) for HL during pregnancy was 82.5% and 90.9% for early (n=62) and advanced stage (n=15). Five-year overall survival (OS) was 97.3% and 100%, respectively. Although not significant, patients with early stage HL appeared to have inferior PFS compared with matched non-pregnant controls (n=62, figure 2), more clearly seen in the subgroup that initiated chemotherapy during pregnancy (n=45). OS was comparable between both groups, supporting the effectiveness of salvage therapy. For advanced stage HL survival was similar to controls, albeit small numbers. Conclusion: Survival of patients diagnosed with early stage HL during pregnancy appears not statistically different from matched non-pregnant controls, however future prospective research is necessary to investigate the efficacy of chemotherapy during pregnancy. Awareness of complications as preterm delivery and low birth weight is important. Disclosure: This project has received funding from the European Union's Horizon 2020 research and innovation program under grant agreement No 647047. We are grateful to the Research Foundation-Flanders (FWO., grant no G070514N) and ESGO (European Society of Gynaecological Oncology) for their support. FA is senior clinical investigator of the F.W.O. MJH was supported by Charles University research project Progres Q28 and Q34 and by grant MH CZ - DRO ('Kralovske Vinohrady University Hospital - FNKV, 00064173'). The funding sources did not influence study design. There are no conflicting interests to declare.